Do social support and self- efficacy play a significant role in substance use relapse? - Mariam A. Al-Ziadat (Health Psychology Research)
This study aims to investigate if social support and self-efficacy play a significant role in substance use relapse. To this end, 197 substance users responded to the modified measures of social support and self-efficacy questionnaire. The participants reported moderate levels of social support and self-efficacy. In addition, the results indicated that there are gender differences in social support level in favour of males and there were differences in social support level in the duration of substance use between less than one year and one year- less than two years also between one year- less than two years and ten years and more in favour of one year- less than two years. Furthermore, the results revealed differences in self-efficacy levels in accordance with substance use status in favour of those without relapse. But there was no difference in self-efficacy level with regard to gender or duration of substance use. Moreover, the findings indicate that self-efficacy and duration of substance use play a significant role in substance use relapse but this is not the case with social support. It was concluded that giving more attention to female social support and to the self-efficacy among substance users are needed.